2021
DOI: 10.3389/fmed.2021.735796
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality of HLH in ICU Regardless Etiology or Treatment

Abstract: Background: Adult hemophagocytic lymphohistiocytosis (HLH) is highly lethal in the ICU. The diagnostic and therapeutic emergency that HLH represents is compounded by its unknown pathophysiological mechanisms. Here, we report on a large cohort of adult HLH in the ICU (ICU-HLH). We analyzed prognostic factors associated with mortality to define the diagnostic and therapeutic challenges in this specific population.Methods: This retrospective study included adult patients diagnosed with HLH in four ICUs in Marseil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Malignancy‐associated‐ and EBV‐positive HLH have historically demonstrated worse survival compared to those with autoimmune or non‐EBV infectious triggers, which may affect treatment outcomes 24–26 . However, as HLH mortality in the ICU is not influenced by underlying etiological triggers and ICU admissions were not drastically different across cohorts, this is less likely the case 27 . Finally, the criteria utilized for treatment response is not a validated tool in the assessment of HLH‐directed therapies so the general applicability of these findings may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy‐associated‐ and EBV‐positive HLH have historically demonstrated worse survival compared to those with autoimmune or non‐EBV infectious triggers, which may affect treatment outcomes 24–26 . However, as HLH mortality in the ICU is not influenced by underlying etiological triggers and ICU admissions were not drastically different across cohorts, this is less likely the case 27 . Finally, the criteria utilized for treatment response is not a validated tool in the assessment of HLH‐directed therapies so the general applicability of these findings may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, HLH precedes the diagnosis of the underlying malignancy ( 17 ). HLH carries a poor prognosis, but in the setting of a malignancy, the prognosis is worse regardless of the patient's age or intervention ( 6 ). A Swedish study reported all patients with malignancy-associated HLH died within of median time of 22 days (range 0–108) following diagnosis of HLH ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In HLH, there is a loss of this cytotoxic cell-mediated regulation, leading to excessive cytokine secretion, uncontrolled inflammation, multiple organ dysfunction, and failure ( 5 ). Mortality from HLH is very high approaching 60% among those treated in the intensive care unit, underscoring the importance of early diagnosis and aggressive intervention ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This cytokine storm is thought to cause multi-organ failure in HLH ( 49 ). Patients with HLH usually have poor prognosis ( 50, 51 ), with the current treatments, mortality rates among HLH in adults are around 60% ( 52 ).…”
Section: Discussionmentioning
confidence: 99%